PENGARUH INTELLECTUAL CAPITAL TERHADAP PROFITABILITY DAN FIRMS VALUE (Studi pada Perbankan Terdaftar di IDX 2016-2019) - Ikhsandinoto, Achmad Basith; Nuzula, Nila Firdausi (FIA UB, 2022)
It has been nearly three decades since civilization has entered a new economic era; this era is known as the Knowledge-Based Economy (KBE). In this era, the source of productivity and business value creation has shifted to intangible assets, also known as Knowledge-Based Capital (KBC). This, of course, is closely related to Intellectual Capital, which has been the topic of research for scholars around the world. However, there are still no clear provisions for measuring Intellectual Capital in a company as well as measuring tangible assets. Various results have also been obtained, as findings from numerous studies vary due to location, research object, and method differences. The purpose of this study was to determine the effect of Intellectual Capital (EVAIC+) on the Firms Value (Market to Book value & Price to Earnings Ratio) with the company's Profitability (Return on Assets & Return on Equity) as an intervening variable. Intellectual capital was measured using Ulum's and Pulic’s Models. The research samples are 80 from 20 banking sector companies listed in Indonesia Stock Exchange (IDX) during the period 2016-2019. Partial least squares analysis has been employed to identify the Intellectual Capital, which predicts Profitability, the Firms Value, and the moderating effect of Profitability on Intellectual and Firms Value relationship. The results showed that: (1) the Intellectual Capital has a negative effect and not significant on Firms Value; (2) Intellectual Capital has a positive and significant impact on Profitability; (3) Profitability has a positive and significant impact to escalate Firms Value; Finally, (4) this study has shown that Profitability serves as an intervening variable in a complete relationship between Intellectual Capital and Firms Value.